UV-induced toxicity of cerium oxide nanoparticles (CeO2 NPs) and the protective properties of natural organic matter (NOM) from the Rio Negro Amazon River - Zhang, Yueyang; Blewett, Tamzin A.; Val, Adalberto Luis; Goss, Greg G. (Environmental Science: Nano, 2018)
Electric power in and transportation to remote communities in the Amazon basin are almost entirely derived from the use of diesel engines. To increase the fuel efficiency and decrease CO2 emissions, cerium oxide nanoparticles (CeO2 NPs) are increasingly used as diesel fuel additives. The waters of the Rio Negro (Amazon, Brazil) have very low ion concentrations (<25 μmol L-1), low pH (<pH 4.5) and high natural organic matter content (>12 mg L-1), all factors which would improve the solubility, dispersibility and bioavailability of CeO2 NPs. Furthermore, the high levels of ultraviolet (UV) radiation present can activate CeO2 NPs given that they are known photocatalytic particles. Thus, the release of CeO2 NPs into the Amazon environment represents the most likely environment for CeO2 NPs to exert any effect. The goals of this study were to determine 1) if toxicity of CeO2 NPs occurs in vivo using a native species, cardinal tetra, 2) if sunlight mediates increased toxicity of CeO2 NPs and 3) if the natural organic matter (NOM) present in Rio Negro waters mitigates or mediates the toxicity of CeO2 NPs. CeO2 NPs were found to produce hydroxyl radicals (·OH) in the presence of artificial sunlight. CeO2 NPs also significantly induced gill lipid peroxidation, but only in the presence of artificial sunlight/on exposure to UV light. CeO2 NPs and UV light were also combined to increase interlamellar cell mass resulting in pathohistological alterations in the gill morphology. The presence of NOM from the Rio Negro (∼13-15 mg L-1) reduced but did not necessarily eliminate these noted effects. © 2018 The Royal Society of Chemistry.